Towards MPGD-based (S)DHCAL. (April 2020) - Shaked Renous, D.; Bhattacharya, P.; Chefdeville, M.; Drancourt, C.; Moleri, L.; Tesi, A.; Coimbra, A.; Breskin, A.; Bressler, S.; Geralis, T.; Kajomovitz, E.; Karyotakis, J.; et al.
Abstract: Digital and Semi-Digital Hadronic Calorimeters ((S)DHCAL) were suggested for future Colliders as part of the particle-flow concept. Though studied mostly with Resistive Plate Chambers (RPC), studies focusing on Micro-Pattern Gaseous Detector (MPGD)-based sampling elements have shown the potential advantages using such techniques. In 2018, eight 48x48 cm 2 sampling elements based on resistive Micromegas and Resistive Plate WELL (RPWELL) technologies were assembled. They were tested within a small MPGD-based SDHCAL prototype incorporating in addition three 16x16 cm 2 Micromegas detectors and steel absorber plates recording hadronic showers of low-energy pions at the CERN/PS beam line. Preliminary results and analysis methodology are presented, using data samples recorded with pions with momenta in the range from 2 to 6 GeV/c.